Effects of genotype, generation and slaughter age on carcass characteristics of indigenous chickens of Bangladesh under intensive system - Faruque, S; Bhuiyan, A K F H; Rana, M M (Bangladesh Journal of Livestock Research, 2021)
The aim of this study was to compare the carcass characteristics of three improved indigenous chicken genotypes at Bangladesh Livestock Research Institute (BLRI), Bangladesh according to genotype, generation, slaughter age and their interactions. The name of chicken genotypes was Non-descript Deshi (ND), Hilly (H) and Naked-neck (NN). A total of 1585 day-old chicks (918 ND, 378 H and 289 NN) were produced to form foundation stocks for their improvement both egg production and growth rate by selection in generations (foundation stock G0; generation G1; generation G2). Selection was practiced firstly at 8 weeks of age (based on breeding value) and secondly, at 40-weeks of age (based on index value). Data on growth traits, egg production and reproductive traits, fertility and egg shell quality of birds were kept and analyzed in a non-orthogonal factorial experiment using the general linear model procedure of SPSS 11.5, 1998. However, this study was carried out on a total of 99 male birds of three chicken genotypes, having 5, 10 and 18 birds of ND, H and NN genotype from each generation, respectively. The close mean body weight of birds were selected according to age at 8, 10 and 12 weeks and sacrificed. Results showed that the dressing percentage was varied (p<0.001) in among the genotypes and slaughter age of birds. Breast meat and thigh plus drumstick meat weight was influenced (p<0.001) genotype, generation, and slaughter age of birds. Wing meat weight was shown differ (p<0.001) for generation of birds. However, carcass traits were observed greater percentage in NN genotype followed by other two genotypes. With increasing of age from 8 to 12 weeks there was a significant (p<0.001) increase proportion of pre-slaughter weight (60.95%) and thigh plus drumstick weight (6.28%). Overall mean of pre-slaughter weight, percent weight of dressing, breast meat, thigh plus drumstick and wing meat of indigenous chicken were 756.9±6.4 g, 66.5±0.1%, 13.4±0.0%, 19.8±0.0% and 6.6±0.0%, respectively. Present results indicate that the carcass characteristics of indigenous chickens can be influenced by genotype, generation and slaughter age under intensive system. Bang. J. Livs. Res. Vol. 28 (1&2), 2021: P. 16-28